2015
DOI: 10.3390/ijms16034372
|View full text |Cite
|
Sign up to set email alerts
|

Cell Membrane CD44v6 Levels in Squamous Cell Carcinoma of the Lung: Association with High Cellular Proliferation and High Concentrations of EGFR and CD44v5

Abstract: Membranous CD44v6 levels in tumors and surrounding samples obtained from 94 patients with squamous cell lung carcinomas were studied and compared to clinical stage, cellular proliferation, membranous CD44v5 levels, epidermal growth factor receptor EGFR and cytoplasmatic concentrations of CYFRA 21.1. CD44v6 positive values were observed in 33/38 non-tumor samples and in 76/94 tumor samples, but there were not statistically significant differences between both subgroups. In CD44v6 positive tumor samples, CD44v6 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Miyoshi et al [ 51 ] showed that CD44v3, CD44v5, CD44v6, or CD44v7 was expressed in 28 of 31 (90.3%) non-small cell lung carcinomas (NSCLCs) tissue samples using RT-PCR, and the expression of the CD44v6 was associated with lymph node metastasis. Recently, it has been shown that CD44v6 expression in NSCLC is associated with squamous subtype, lymph node metastasis, and a poor survival and should be considered as a new important prognostic marker [ 52 54 ].…”
Section: Different Cd44v Association With Cancer Progressionmentioning
confidence: 99%
“…Miyoshi et al [ 51 ] showed that CD44v3, CD44v5, CD44v6, or CD44v7 was expressed in 28 of 31 (90.3%) non-small cell lung carcinomas (NSCLCs) tissue samples using RT-PCR, and the expression of the CD44v6 was associated with lymph node metastasis. Recently, it has been shown that CD44v6 expression in NSCLC is associated with squamous subtype, lymph node metastasis, and a poor survival and should be considered as a new important prognostic marker [ 52 54 ].…”
Section: Different Cd44v Association With Cancer Progressionmentioning
confidence: 99%
“…CD44v6 is a soluble intercellular adhesion molecule, which is closely related to the invasion, progression and metastasis of malignant tumors [ 11 ]. CD44s and CD44V6 were predominantly present in normal lung tissue [ 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have found that the essential factor of nodular growth is the unlimited expansion and invasion of tumor [5,6]. Studies at home and abroad [7][8][9][10][11][12][13][14][15] have found that cyclooxygenase-2 (COX-2), Ki67, vascular endothelial growth factor (VEGF), CD44V6, epidermal growth factor receptor (EGFR), double microsome 2 (MDM2) and transforming growth factor TGF-β1 have certain clinical significance in tumor growth. However, the role of these immune indexes in the early stage of tumor, that is, the growth of malignant pulmonary nodules, has not been studied.…”
Section: Introductionmentioning
confidence: 99%
“… 9 , 10 The prognostic value of CD44v6 has been reported in various types of tumors, including gastric cancer, hepatocellular carcinoma, esophageal cancer, lung cancer, head and neck squamous cell carcinoma, and osteosarcoma. 11 16 With respect to breast cancer, the relationship between CD44v6 and prognosis was still controversial. 17 19 To address this issue, we conducted a meta-analysis of all the eligible studies to evaluate the predictive value of CD44v6 in clinicopathological features and prognosis of breast cancer.…”
Section: Introductionmentioning
confidence: 99%